PENGARUH KREATIVITAS DAN MOTIVASI TERHADAP MINAT BERWIRAUSAHA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ISLAM MALANG - Safitri Tasidjawa; Moh. Amin; Afifudin Afifudin (Universitas Islam Malang, 2021)
Entrepreneurs can play a significant role in realizing the quality of society and the nation, one of which is instilling an entrepreneurial spirit and spirit. In addition to creativity, another factor that influences interest in entrepreneurship is entrepreneurship motivation because interest in entrepreneurship without motivation will not work in accordance with the abilities of an entrepreneur. interest in starting a business. So the main problem in the world of entrepreneurship (entrepreneurs) faced by someone is the lack of management experience or weak decision-making abilities are the main problems of business failure. Based on the above background, the importance of creativity and entrepreneurial motivation is one of the efforts to increase student interest in entrepreneurship. The focus of this research, especially students of the Faculty of Economics and Business, Islamic University of Malang, is expected to be able to shape the mindset, attitude, and behavior to become an entrepreneur (entrepreneur) so as to direct them to choose entrepreneurship as a career choice. Keywords: creativity, motivation, interest in entrepreneurship